UPAYA PENINGKATAN KESEHATAN REPRODUKSI CALON PENGANTIN WANITA MELALUI PENDAMPINGAN PERENCANAAN KEHAMILAN SEHAT DI KUA KALIWATES KABUPATEN JEMBER - Riza Umami; Sutrisno Sutrisno; Syaiful Bachri (Politeknik Kesehatan Kemenkes malang, 2021)
A healthy pregnancy requires physical and psychological preparation which a mother-to-be must prepare before pregnancy occurs. In this regard, the impact of the unprepared mother-to-be can actually lead to a risky pregnancy that can lead to maternal death. Premarital health promotion aims to improve the community's ability to maintain and improve their health, namely premarital reproductive health, in this activity focused on planning healthy pregnancies. The purpose of this activity is that the prospective bride is able to plan a healthy pregnancy. Community service activities are carried out at KUA Kaliwates, Jember Regency with a target number of 35 CPW. The activity plan went through several stages, namely FGD training and assistance in planning healthy pregnancies and evaluating activities.The output of this activity is in the process of publication in an accredited National Journal and making a booklet with the title